Corporate Social Responsibility and Inter-Organisational Trust in a B2B Context - Egle Staniskiene; Zivile Stankeviciute; Asta Daunoriene (Kvalita Inovácia Prosperita, 2019)
Purpose: The purpose of the paper to reveal the linkage between the customer perception of the supplier’s CSR and inter-organisational trust in a B2B context.